PERMAINAN POHON ANGKA BERBASIS RAMAH ANAK UNTUK MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK USIA 4–5 TAHUN DI TKK REGINA PACIS BAJAWA - Maria Rosvita Isang; Andi Nafsia; Gde Putu Arya Oka; Yasinta Maria Fono (STKIP Pesisir Selatan, 2026)
The objective of this study is to determine whether the use of child-friendly number tree games can enhance the cognitive development of children aged 4–5 years at TKK Regina Pacis Bajawa. This study employs a qualitative research method with a descriptive approach. Data collection techniques included interviews with teachers and observations of children's activities. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing, with data validity tested using triangulation. The results show that the number tree game yields positive outcomes for early childhood cognitive development. This is evident from observations of 14 children: 9 children reached the Very Well Developed category, 3 children were in the Developed as Expected category, and 2 children were in the Starting to Develop category. Consequently, the number tree game is declared effective as a learning medium to improve cognitive abilities, particularly in recognizing and naming numerical symbols 1–10 for children aged 4–5 years.